2004
DOI: 10.1021/la035479y
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin Adsorption onto Polyelectrolyte Multilayer Films

Abstract: The Layer-by-layer deposition of positively and negatively charged macromolecular species is an ideal method for constructing thin films incorporating biological molecules. We investigate the adsorption of fibronectin onto polyelectrolyte multilayer (PEM) films using optical waveguide lightmode spectroscopy (OWLS) and atomic force microscopy (AFM). PEM films are formed by adsorption onto Si(Ti)O2 from alternately introduced flowing solutions of anionic poly(sodium 4-styrenesulfonate) (PSS) and cationic poly(al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 62 publications
0
70
0
Order By: Relevance
“…Ngankam et al 31 showed that the positively charged, PAH terminated PEM films adsorbed denser FN layer and favorably influenced the distribution of FN molecules by inhibiting their aggregation in the adsorption layer when compared to negative-terminal layers. 31 The density and thickness of FN on a PAH-terminated film were roughly double those on a negatively charged PSS-terminated film. It was also shown that the adsorption of the FN onto polyelectrolyte films such as poly(L-lysine) is a more important factor in controlling cell-materials interactions than film charge and layer number.…”
Section: N-pemus Regulate Ecm Adsorptionmentioning
confidence: 99%
“…Ngankam et al 31 showed that the positively charged, PAH terminated PEM films adsorbed denser FN layer and favorably influenced the distribution of FN molecules by inhibiting their aggregation in the adsorption layer when compared to negative-terminal layers. 31 The density and thickness of FN on a PAH-terminated film were roughly double those on a negatively charged PSS-terminated film. It was also shown that the adsorption of the FN onto polyelectrolyte films such as poly(L-lysine) is a more important factor in controlling cell-materials interactions than film charge and layer number.…”
Section: N-pemus Regulate Ecm Adsorptionmentioning
confidence: 99%
“…Intense amide-I and amide-II bands at 1654 and 1547 cm À1 were obtained, which are diagnostic for protein binding or accumulation at the PEM/water interface. According to classical amide-band-assignment papers, [40][41][42][43] these band positions indicate further that HSA is an a-helix-rich protein. No large variations of the band intensities were observed as a function of time in each of the three sets, which suggests rapid sorption processes and adsorption saturation after around an hour.…”
Section: Influence Of Pem Thicknessmentioning
confidence: 99%
“…18,19 Increasingly, polyelectrolyte multilayers (PEMs) are used as bioactive substrata for the study of cell adhesion or phenotype. 14,[20][21][22][23][24][25][26] PEMs are polyelectrolyte complexes fabricated via a layer-by-layer (LbL) assembly process with dilute solutions of positively and negatively charged polymers or by the LbL assembly of weakly interacting hydrogen bond acceptors/donors with polyelectrolyte polymers of complementary polarity. Because the physical properties and film thickness of weak (pHsensitive) PEMs can be controlled with high precision through assembly conditions such as solution pH, these materials find utility in a range of applications including but not limited to cytophilic substrata and cytophobic coatings.…”
Section: Introductionmentioning
confidence: 99%